Investigation of the effects of bovine collagen peptides and mixed berries on rheological properties and biological activity of egg white-based beverage via central composite design - Varga-Tóth, Adrienn; Németh, Csaba; Dalmadi, István; Csurka, Tamás; Csorba, Renáta; Elayan, Majd; Enkhbold, Munkhnasan; Hidas, Karina; Friedrich, László Ferenc (Frontiers in Nutrition, 2023)
Modern consumer expectations have become highly diversified: they want more opportunities to meet diverse family needs (diversity of family members in age, gender, physical activity, etc.) and individual health goals with a huge variety of sensorial preferences. Our research is aimed to develop a protein-dense, highly bioactive, lactose- and whey protein-free beverage applying a central composite rotational design (CCRD) with 2 factors. For this purpose, an egg white-based beverage was flavored with mixed berries (factor A) and enriched with bovine collagen peptides (factor B). After suitable sample preparation, the rheological properties were investigated by an Anton Paar MCR 92 rheometer (with CC 27 system, and flow behavior was analyzed with a Herschel-Bulkley (H-B) model). The antioxidant capacity of samples was investigated by Ferric Reducing Antioxidant Power (FRAP) method, total anthocyanin content was estimated based on a spectrophotometric method and the total phenolic content was determined by the Folin Ciocalteu method. Our results are figured on respond surfaces demonstrating that both factors and their interactions show a positive correlation with the examined parameters. Based on the CCRD, all investigated parameters are significantly influenced by at least one aspect and can be adequately estimated for further product development.